DESAIN TAMPILAN ANTARMUKA SISTEM INFORMASI DI RSGM PROF. SOEDOMO YOGYAKARTA - , NOHAN ARUM ROMADLONA, Nur Rokhman, S.Si., M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Hospital information system is helpful in the hospital management decisions quickly and accurately and in the Technical Instructions Permenkes 1171/Menkes/VI/2011 about Hospital Information System Article 1 states that each hospital shall implement a hospital information system. Dental Hospital, RSGM Prof. Soedomo have to use hospital information system desktop-based made by the medical records officer who had worked there. However, there is no handover hospital information system to users and to the officer of Information Technology (IT) in the RSGM Prof. Soedomo and this time it is not possible to have recourse to the system. This makers who cause many problems in the use of hospital information system. Based on interviews and analysis of the hospital information system, it found various deficiencies on them look less up to date, can not be developed, common errors, loading response is very slow, there are some users' needs were not being met, and yet there is a distribution of access rights. Purpose: The purpose of design is to make the user interface design of the hospital information system at RSGM Prof. Soedomo tailored to the needs of users in hospitals to maximize the system in order to create a quick and precise service. Results: Based on the user requirements analysis and interviews to IT officers, registration officers, medical records officers, pharmacy officers, cashier, and nurses, the researchers designed the look of the design of hospital information systems that meet user needs in order to maximize the services. Hospital information system design consists of patient registration module, the module polyclinics, medical record module, modules and module pharmacy cashier. The design of the display interface design can be used as a reference for IT officers as programmer in making full hospital information system